Cell and developmental biology of arbuscular mycorrhiza symbiosis - Gutjahr, Caroline; Parniske, Martin (Annual review of cell and developmental biology, 2013)
The default mineral nutrient acquisition strategy of land plants is the symbiosis with arbuscular mycorrhiza (AM) fungi. Research into the cell and developmental biology of AM revealed fascinating insights into the plasticity of plant cell development and of interorganismic communication. It is driven by the prospect of increased exploitation of AM benefits for sustainable agriculture. The plant cell developmental program for intracellular accommodation of AM fungi is activated by a genetically defined signaling pathway involving calcium spiking in the nucleus as second messenger. Calcium spiking is triggered by chitooligosaccharides released by AM fungi that are probably perceived via LysM domain receptor kinases. Fungal infection and calcium spiking are spatiotemporally coordinated, and only cells committed to accommodating the fungus undergo high-frequency spiking. Delivery of mineral nutrients by AM fungi occurs at tree-shaped hyphal structures, the arbuscules, in plant cortical cells. Nutrients are taken up at a plant-derived periarbuscular membrane, which surrounds fungal hyphae and carries a specific transporter composition that is of direct importance for symbiotic efficiency. An elegant study has unveiled a new and unexpected mechanism for specific protein localization to the periarbuscular membrane, which relies on the timing of gene expression to synchronize protein biosynthesis with a redirection of secretion. The control of AM development by phytohormones is currently subject to active investigation and has led to the rediscovery of strigolactones. Nearly all tested phytohormones regulate AM development, and major insights into the mechanisms of this regulation are expected in the near future.